PhI(OAc)2 mediated decarboxylative sulfonylation of β-aryl-α,β-unsaturated carboxylic acids: A synthesis of (E)-vinyl sulfones - Praewpan Katrun (2018)
© The Royal Society of Chemistry 2015. A highly efficient metal-free decarboxylative sulfonylation protocol for the preparation of (E)-vinyl sulfones from of β-aryl-α,β-unsaturated carboxylic acids using sodium sulfinates and (diacetoxyiodo)benzene (PhI(OAc)2) was developed. This strategy offers a simple and expedient synthesis of (E)-vinyl sulfones bearing a wide variety of functional groups. A radical-based pathway has been proposed for this decarboxylative sulfonylation reaction.